A Comparison of Climate Change Mitigation and Adaptation Strategies for the Construction Industries of Three Coastal Territories. (16th August 2011) - Gunawansa, Asanga; Kua, Harn Wei
ABSTRACT The success of climate change strategies depends on how well mitigation and adaptation measures are implemented. It is especially important to implement effective mitigation and adaptation measures in coastal territories because they will be more directly affected by some of the possible effects of climate change. This study assessed and compared how Singapore, Miami‐Dade and San Francisco – three coastal territories – implement climate change strategies in their construction industries. Case study method – in which primary and secondary information was collected and analyzed – was used. It was found that these three territories have a few similarities; for example, Singapore and San Francisco mandate green building requirements, whereas Singapore and Miami‐Dade do not explicitly consider adaptation measures in their building codes. It was also noted that although mitigation has entered mainstream policy‐making, adaptation still lags behind. Consequently, this study has proposed a few lessons; for example, policy‐makers in Singapore and Miami‐Dade should complement existing measures with platforms to engage the public on disaster management. Copyright © 2011 John Wiley & Sons, Ltd and ERP Environment.